(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Abstract - This study explores how artificial intelligence (AI) might improve financial decision-making for small and medium-sized businesses (SMEs) and micro, small, and medium-sized enterprises (MSMEs). These businesses are essential to the growth of the world economy, but they continue to confront obstacles such restricted access to resources, a lack of financial know-how, and a lack of up-to-date information for wise decision-making. Artificial intelligence (AI)-powered technologies like natural language processing, machine learning algorithms, and predictive analytics provide creative answers to these problems. MSMEs and SMEs may more efficiently anticipate financial trends, evaluate risks, allocate resources optimally, and find new income streams by using AI technology.